2020
DOI: 10.1007/s00296-020-04699-x
|View full text |Cite
|
Sign up to set email alerts
|

High rates of severe disease and death due to SARS-CoV-2 infection in rheumatic disease patients treated with rituximab: a descriptive study

Abstract: The objective of this study is to describe the characteristics and outcomes of rheumatic and musculoskeletal disease (RMD) patients who were treated with rituximab and had suspected or confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In this descriptive study, RMD patients who were treated with rituximab in the last 12 months at the Rheumatology Department of our hospital were screened for SARS-CoV-2 infection via telephone interview and a comprehensive review of clinical healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
1
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 23 publications
5
100
1
13
Order By: Relevance
“…Moreover, the effect of B-cell depleting therapy on COVID-19 outcomes needs to be addressed, although very limited data to date suggest the potential for detrimental effects. [148][149][150] Overall, the findings of pathogenic adaptive immune responses in COVID-19 further support the notion that the timely implementation of immunomodulatory therapy in selected patients may be beneficial.…”
Section: Article In Pressmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, the effect of B-cell depleting therapy on COVID-19 outcomes needs to be addressed, although very limited data to date suggest the potential for detrimental effects. [148][149][150] Overall, the findings of pathogenic adaptive immune responses in COVID-19 further support the notion that the timely implementation of immunomodulatory therapy in selected patients may be beneficial.…”
Section: Article In Pressmentioning
confidence: 56%
“…156,182,183 Recently, D 1 5 3 X X2 small studies reported high rates of severe COVID-19 and mortality in patients on RTX for various indications. 148,149 However, larger studies and longer followup are needed to confirm these observations.…”
Section: Commonly Used Drugs In Sle and Predisposition To Viral Infecmentioning
confidence: 99%
“…Although the study by Loarce-Martos et al [1] was limited by its small sample size, it does however indicate a possibility for differential risk of adverse clinical outcomes among patients with systemic rheumatic disease based on the type of biological agents received. Particularly, rituximab causes B cell depletion that can be associated with decreased antibody production.…”
mentioning
confidence: 95%
“…We read with interest the descriptive study by Loarce-Martos et al [1] to investigate the clinical characteristics and outcomes of patients with systemic rheumatic disease receiving rituximab who acquired coronavirus disease 2019 (COVID-19) or were presumed to acquire COVID-19 in a Spanish hospital. It was reported in the study that patients with systemic rheumatic disease receiving rituximab had unfavorable prognosis upon hospitalization with COVID-19, of which all experienced clinical worsening upon hospitalization and three out of eight hospitalized patients succumbed to death.…”
mentioning
confidence: 99%
“…8 Recently, Loarce-Martos et al confirmed that COVID-19 is not only common, but also particularly severe in patients with rheumatic disease who had been on treatment with RTX. 9 Indeed, in an observational study they reported that 13 out of 76 (17.1%) patients with rheumatic disease treated in their centre with RTX in the last 12 months prior to screening for the presence of SARS-CoV-2 had suspected or confirmed infection. A total of eight of these patients (61.5%) developed severe COVID-19 leading to hospitalisation, from which five (38.5%) fulfilled the acute respiratory distress syndrome criteria, whereas three (23.1%) eventually died.…”
mentioning
confidence: 99%